Beyond Forced Migration: The Narrative Communication in the Resilience of Cipaku's Displaced Communities - Hariyati, Farida; Lubis, Djuara P.; Kinseng, Rilus A.; Sumardjo , Sumardjo (The Institute of Research and Community Service (LPPM) - Universitas Lancang Kuning, 2024)
This qualitative study explores the resilience of Cipaku's displaced communities through narrative communication, shedding light on the unique sociolinguistic dynamics of development-induced displacement. Anchored in the Communication Theory of Resilience (CTR), it delves into how displaced individuals employ communicative processes. The study focused on interviews with 12 individuals selected using snowball sampling technique from Cipaku Village who have lived through displacement more than 10 years due to forced migration, and supported with field observation to gain documentation in capturing their memories and subsequent positive adaptations. Data was analyzed using the NVivo 12 Plus software, which facilitated the organization, coding, and thematic analysis relevant to the study's objectives. The findings of this research delves into how displaced individuals employ communicative processes; crafting normalcy, affirming identity, maintaining networks, employing alternative logics, and foregrounding positive actions to navigate the upheavals of displacement. It highlights how displaced populations actively reconstruct their social realities, preserve cultural identities, and sustain community cohesion through narrative communication. This study also points to gaps in understanding the erosion of linguistic diversity within displaced communities and recommends further exploration of digital communication's role in sustaining displaced communities' communicative networks.